5x – 10 = 3x – 10 – (x – 2 )

First you must multiply the x – 2 by -1 **before** you begin your steps of solving. The – (x – 2 ) is the same as – 1(x – 2 ) . So 5x – 10 = ???? ** **

** I want the x-terms on the left side of the “=” and the number terms on the right side. But first simplify the right side. You will make fewer mistakes. ** 5x – 10 = 3x – 10 – x +2. You do know why the 2 is positive?

Simplifies to 5x-10 = 2x – 8. ** **

**NOW begin solving. ** **I will begin solving: Subtract 2x from both sides.**

** **This is how we “move the x-term” to the left side of the equation.

3x – 10 = – 8 Now **ADD 10 **to both sides. This is how we **move the “-10 term” to the right side** of the equation.

Did you notice that the 10 is negative, and that it is on the left side of the equation?

3x – 10 **+ 10** =-8** + 10 ****This becomes:** 3x =2

How do we finish with** 1x** instead

of 3x? D**ivide by 3 ormultiply by 1/3 .**

Thus 3x =2 becomes 3x/3 = 2/3 , I **divided by 3 (or multiplied by 1/3). So we know x= 2/3. **

** YES, divide by 3 or multiply by 1/3 are the same!!**

Thanks